2018
DOI: 10.1111/joor.12657
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of brain mechanisms of chewing and clenching movements

Abstract: Functional magnetic resonance imaging (fMRI) is widely used for investigating brain activation patterns associated with chewing and clenching movements. Whether studies consistently identify similar brain loci engaged in these movements remains unknown. We investigated the consistency with which specific brain loci were reported to be activated during teeth-occluding movements, using the activation likelihood estimation (ALE) meta-analysis. Twenty fMRI studies that used fMRI to investigate brain activation dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 62 publications
7
35
1
Order By: Relevance
“…These findings have been further replicated in different studies . By evaluating multiple studies of the same kind, a meta‐analysis confirmed the previous hypothesis that the primary motor and somatosensory cortices are the key regions where activation corresponds to the chewing movement . The findings also corroborate evidence from animal models, which revealed that activity of the masticatory motor area and sensory input from the facial somatosensory area are necessary for mastication …”
Section: What Can Neuroimaging Research Tell Us?supporting
confidence: 76%
See 4 more Smart Citations
“…These findings have been further replicated in different studies . By evaluating multiple studies of the same kind, a meta‐analysis confirmed the previous hypothesis that the primary motor and somatosensory cortices are the key regions where activation corresponds to the chewing movement . The findings also corroborate evidence from animal models, which revealed that activity of the masticatory motor area and sensory input from the facial somatosensory area are necessary for mastication …”
Section: What Can Neuroimaging Research Tell Us?supporting
confidence: 76%
“…Earlier research began by asking the “where” question, as shown in the pioneering work by Onozuka et al, who identified the activation of multiple brain regions, primarily the sensorimotor area, corresponding to the chewing movement. These findings have been further replicated in different studies . By evaluating multiple studies of the same kind, a meta‐analysis confirmed the previous hypothesis that the primary motor and somatosensory cortices are the key regions where activation corresponds to the chewing movement .…”
Section: What Can Neuroimaging Research Tell Us?supporting
confidence: 72%
See 3 more Smart Citations